Study of the Impact and Mechanism of Gypsum Binder Hydration Process in the Presence of Nanomodifiers - Derevianko, Victor; Дерев’янко, Віктор Миколайович; Kondratieva, Natalia; Кондратьєва, Наталія Вікторівна; Hryshko, Hanna; Гришко, Ганна Миколаївна (Taras Shevchenko National University, 2018)
This article represents the results of the research of nanomodification of mineral binders involving structure formation mechanisms and gypsum binder hydration process, and thus, affecting various properties. Experiments proved that during growth, crystals partly penetrate into each other and form a three-dimensional network permeating and incorporating the entire gypsum stone into a whole body, which promotes structuring of calcium sulfate matrix and improvement in gypsum compressive strength up to 30%. Chemical functionalization of the surface of carbon nanotubes promotes a reduced sedimentation effect, allows for a more uniform nanostructure dispergation throughout the modified material volume and provides chemical interaction between the substance matrix and nanotubes.У цій статті наведено результати дослідження наномодифікації мінеральних в’яжучих за участю механізмів структуроутворення та процесу гідратації гіпсової в’яжучої речовини, що впливає на різні властивості. Експериментально доведено, що під час росту кристали частково проникають один в одного і утворюють тривимірну мережу, яка пронизує і об'єднує весь гіпсовий камінь в ціле тіло, що сприяє структуруванню матриці сульфату кальцію і підвищенню міцності гіпсу на стиск до 30%. Хімічна функціональність поверхні вуглецевих нанотрубок сприяє зниженню ефекту седиментації, забезпечує більш рівномірну диспергацію наноструктури по всьому об’єму модифікованого матеріалу та забезпечує хімічну взаємодію між матрицею речовини та нанотрубками.
Дослідження впливу та механізму процесу гідратації гіпсового в’яжучого в присутності наномодифікаторів
Keywords: carbon nanotubes; вуглецеві нанотрубки; calcium sulfate hemihydrate; півгідрат сульфату кальцію; modification; модифікація; hydration; гідратація; calcium sulfate matrix; матриця сульфату кальцію